1996
DOI: 10.1063/1.361445
|View full text |Cite
|
Sign up to set email alerts
|

Film quality in relation to deposition conditions of a-SI:H films deposited by the ‘‘hot wire’’ method using highly diluted silane

Abstract: The deposition parameter space has been extensively explored using the hot wire technique with 1% SiH4 in He as a source gas. To achieve reasonable deposition rates despite the high dilution, the filament was positioned at 1–2 cm from the substrate. This short distance introduced a large nonuniformity across the substrate in deposition rate as well as in film properties. These spatial variations were used to analyze which factors in the deposition determine film quality. Radiation from the filament as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…In the low pressure, collisionless regime, these wire-desorbed radicals may act as the primary film deposition precursors, while at higher pressure, they may react with other species in the gas phase to produce the precursors. In particular, the study by Molenbroek et al 1 suggested a direct correlation between amorphous film quality and the degree of reaction of wiregenerated Si in the gas phase.…”
Section: Introductionmentioning
confidence: 99%
“…In the low pressure, collisionless regime, these wire-desorbed radicals may act as the primary film deposition precursors, while at higher pressure, they may react with other species in the gas phase to produce the precursors. In particular, the study by Molenbroek et al 1 suggested a direct correlation between amorphous film quality and the degree of reaction of wiregenerated Si in the gas phase.…”
Section: Introductionmentioning
confidence: 99%
“…The probability for these reactions, however, is limited due to the relatively low SiH 4 pressure and small distance between filament and substrate ͑typically р5 cm͒. It is expected that a considerable fraction of the ͑hot͒ Si atoms can react with SiH 4 ͑to mainly H 2 SiSiH 2 ), 63,78 but this is less evident for H. It is rather improbable that H reacts to SiH 3 in the gas phase and the proposed scheme that SiH 3 is created at the a-Si:H surface by H ͑i.e., H creates a surface dangling bond by H abstraction and this surface dangling bond abstracts subsequently a H atom from SiH 4 ) 78 is also unlikely because of the very low reactivity of SiH 4 with pristine crystalline Si surfaces. 79,80 It can therefore be excluded that in HWCVD SiH 3 contributes dominantly to film growth.…”
mentioning
confidence: 99%
“…2). Hence, it is clear that triplet silylsilylene will cross sooner or later to singlet state, which easily isomerizes to singlet disilene H 2 SiSiH 2 ( 1 A g ) [51,54]. If the crossing between the two systems is fast, vibrationally excited H 3 SiSiH( 3 A 00 ) produced from collisions between SiH 4 and Si( 3 P) can be converted to excited singlet and then may dissociate to Si(H 2 )Si( 1 A 1 ) + H 2 at low pressure.…”
Section: Unimolecular Bimolecularmentioning
confidence: 99%